Behavior of SD-OCT Detectable Hyperreflective Foci in Diabetic Macular Edema Patients after Therapy with Anti-VEGF Agents and Dexamethasone Implants. (14th April 2021) - Rübsam, Anne; Wernecke, Laura; Rau, Saskia; Pohlmann, Dominika; Müller, Bert; Zeitz, Oliver; Joussen, Antonia M.
Abstract : Purpose . Diabetic macular edema (DME) is the most common cause of blindness in the working-age population. Spectral-domain optical coherence tomography (SD-OCT) allows detection and monitoring of the edema and a detailed analysis of the retinal structure. Hyperreflective foci (HF) are small, circumscribed lesions on OCT, and their origin is yet to be determined. Our study was aimed to shed light on HF pathophysiology, by analyzing their number and location in DME patients at baseline and after therapy. Methods . A prospective, observational study on 59 eyes of 51 DME patients who were treated with antivascular endothelial growth factor (VEGF) therapy (VEGF group, n = 40 eyes) or dexamethasone implant (DEX group, n = 19 ). HF and hard exudates (HE) were discriminated by their appearance on fundus photographs and their size on OCT. Quantity and location of HF and HE were analyzed at baseline and after therapy. Results . DME decreased in 75% of patients in the VEGF (455.5 μ m vs. 380.8 μ m, p = 0.02 ) and in 95% of patients in the DEX group (471.6 μ m vs. 381.9 μ m, p = 0.007 ). The number of foci decreased in 62.5% of patients after anti-VEGF (130.6 vs. 111.1, p = 0.07 ) and in 68% of patients after dexamethasone injection ((123.4 vs. 94.9, p = 0.02 ) 5.1). A subgroup of 15% of eyes, all treated with anti-VEGF, showed accumulation of larger HF in outer retinal layers to visible HE during DME resolution, whereas smaller HF, found in all retinal layers, remained unchanged. There was a trend towards a dynamic shift of the foci from inner to outer retinal layers. Conclusion . The dynamic rearrangement of the small HF and their slightly greater reduction after anti-inflammatory therapy suggest inflammatory cells as their origin, whereas larger HF in the outer retinal layers correspond to microexudates. Furthermore, we found a more favourable outcome in patients with HF after treatment with dexamethasone implants compared to anti-VEGF agents.